2000
DOI: 10.1007/bf02988206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of iodinated and brominated [11C]styrylxanthine derivatives asin vivo radioligands mapping adenosine A2A receptor in the central nervous system

Abstract: In vivo assessment of the adenosine A2A receptors localized in the striatum by PET or SPECT offers us a new diagnostic tool for neurological disorders. In the present study, we evaluated the potential of iodinated and brominated styrylxanthine derivatives labeled with 11C as an in vivo probe. [7-Methyl-11C]-(E)-3,7-dimethyl-8-(3-iodostyryl)-1-propargylxan thine ([11C]IS-DMPX) and [7-methyl-11C]-(E)-8-(3-bromostyryl)-3,7-dimethyl-1-propargylxa nthine ([11C]BS-DMPX) were prepared by the 11C-methylation of corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…11 C labeled ( E )-8-(3-chlorostyryl)-1,3-dimethyl-7-[ 11 C]methylxanthine ([ 11 C]CSC, 50 ) proved to accumulate in the striatum, and PET studies on rabbits showed a fast brain uptake of [ 11 C]CSC, reaching a maximum in less than 2 min [122]. Further styrylxanthine derivatives labeled with 11 C were tested as in vivo probes [123]. [7-Methyl- 11 C]-( E )-3,7-dimethyl-8-(3-iodostyryl)-1-pro-pargylxanthine ([ 11 C]IS-DMPX, 91 ) and [7-methyl- 11 C]-( E )-8-(3-bromostyryl)-3,7-dimethyl-1-propargylxanthine ([ 11 C]BS-DMPX, 92 ) showed K i affinities of 8.9 and 7.7 nM respectively, and high A 2A /A 1 selectivity values.…”
Section: Radioligands For In Vivo Pet Imaging Of Adenosine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 C labeled ( E )-8-(3-chlorostyryl)-1,3-dimethyl-7-[ 11 C]methylxanthine ([ 11 C]CSC, 50 ) proved to accumulate in the striatum, and PET studies on rabbits showed a fast brain uptake of [ 11 C]CSC, reaching a maximum in less than 2 min [122]. Further styrylxanthine derivatives labeled with 11 C were tested as in vivo probes [123]. [7-Methyl- 11 C]-( E )-3,7-dimethyl-8-(3-iodostyryl)-1-pro-pargylxanthine ([ 11 C]IS-DMPX, 91 ) and [7-methyl- 11 C]-( E )-8-(3-bromostyryl)-3,7-dimethyl-1-propargylxanthine ([ 11 C]BS-DMPX, 92 ) showed K i affinities of 8.9 and 7.7 nM respectively, and high A 2A /A 1 selectivity values.…”
Section: Radioligands For In Vivo Pet Imaging Of Adenosine Receptorsmentioning
confidence: 99%
“…[7-Methyl- 11 C]-( E )-3,7-dimethyl-8-(3-iodostyryl)-1-pro-pargylxanthine ([ 11 C]IS-DMPX, 91 ) and [7-methyl- 11 C]-( E )-8-(3-bromostyryl)-3,7-dimethyl-1-propargylxanthine ([ 11 C]BS-DMPX, 92 ) showed K i affinities of 8.9 and 7.7 nM respectively, and high A 2A /A 1 selectivity values. Unfortunately, biological studies proved that the two ligands were only slightly concentrated in the striatum, and that the two compounds were not suitable as in vivo ligands because of low selectivity for the striatal A 2A receptors and a high degree of nonspecific binding [123]. A useful A 2A PET ligand for in vivo imaging proved to be [ 11 C]KF18446 ( 93 ), also named ( 11 C)TMSX [124].…”
Section: Radioligands For In Vivo Pet Imaging Of Adenosine Receptorsmentioning
confidence: 99%
“…This molecule was shown to accumulate in the striatum, and PET studies on rabbits showed a fast brain uptake of [ 11 C]CSC, reaching a maximum in less than 2 min (Marian et al 1999). Few years later, iodinated and brominated styrylxanthine derivatives labeled with 11 C were tested as in vivo probes (Ishiwata et al 2000c). [7-Methyl- 11 C]-( E )-3,7-dimethyl-8-(3-iodostyryl)-1-propargylxanthine ([ 11 C]IS-DMPX) and [7-methyl- 11 C]-( E )-8-(3-bromostyryl)-3,7-dimethyl-1-propargylxanthine ([ 11 C]BS-DMPX) showed K i affinities of 8.9 and 7.7 nM respectively, and high A 2A /A 1 selectivity values.…”
Section: Xanthine Derivatives Used As Molecular Probesmentioning
confidence: 99%
“…[7-Methyl- 11 C]-( E )-3,7-dimethyl-8-(3-iodostyryl)-1-propargylxanthine ([ 11 C]IS-DMPX) and [7-methyl- 11 C]-( E )-8-(3-bromostyryl)-3,7-dimethyl-1-propargylxanthine ([ 11 C]BS-DMPX) showed K i affinities of 8.9 and 7.7 nM respectively, and high A 2A /A 1 selectivity values. Unfortunately, biological studies proved that the two ligands were only slightly concentrated in the striatum, and that they were not suitable as in vivo ligands because of low selectivity for the striatal A 2A receptors and a high nonspecific binding (Ishiwata et al 2000c). …”
Section: Xanthine Derivatives Used As Molecular Probesmentioning
confidence: 99%
“…Further investigation of [ 11 C]KF17837 showed this radiotracer had poor selectivity for A 2A , as additional binding sites were subsequently identified. However, despite the good in vitro affinity and selectivity for A 2A , [ 11 C]IS-DMPX and [ 11 C]BS-DMPX displayed high nonspecific binding and limited selectivity for the target in vivo, indicating that these radiotracers were not suitable for imaging of A 2A in brain (Ishiwata et al 2000d). These radiotracers had similar properties to [ 11 C] KF17837 and thus, were deemed unsuitable for in vivo imaging of A 2A receptors in brain ).…”
Section: Radiotracers For Imaging a 2a Receptors In Brainmentioning
confidence: 99%